Measurement of CSF core AD biomarkers for routine clinical diagnosis: Do fresh vs frozen samples differ?: Biomarkers (non‐neuroimaging) / Multi‐modal comparisons. (7th December 2020) - Bellomo, Giovanni; Cataldi, Samuela; Paciotti, Silvia; Parnetti, Lucilla
Abstract: Background: Cerebrospinal fluid amyloid‐beta (Aβ) 1‐42/1‐40 ratio, threonine‐181‐phosphorylated‐tau (p‐tau) and total‐tau (t‐tau) represent core AD biomarkers. The wide availability of automated platforms has represented a high achievement for reducing the pre‐analytical variability of these determinations in routine clinical setting. With respect to classical manual ELISAs, these platforms give us also the possibility to measure any single sample and to get the result within approx. 30 min. So far, reference values are represented by measurements obtained in frozen samples. In this work, we wanted to check if the values obtained in fresh CSF differ from those obtained in frozen samples. This issue could be crucial in routine diagnostic work. Method: Thirty‐seven consecutive CSF samples have been analyzed immediately after lumbar puncture and after one‐month deep freezing (‐80°C). As automated platform we used LUMIPULSE G600‐II. The fresh aliquot has been analyzed in its storage tube. Result: As shown in Table 1, in fresh samples an increase of Aβ1‐40, Aβ1‐42 and t‐tau was observed as compared to frozen samples. Aβ1‐42/Aβ1‐40 ratio and p‐tau – ie, the mandatory parameters for diagnosis of Alzheimer disease ‐ showed no variations. With respect to the AD profile according to the A/T/(N) criteria for AD diagnosis (Jack et al., 2018), no changes in classification were observed when comparing results obtained in fresh vs frozen samples. Conclusion: No differences in Aβ1‐42/Aβ40 ratio, p‐tau and t‐tau were observed in fresh vs frozen samples. According to these data, it seems not necessary to define new cut‐offs for fresh samples. Nevertheless, further larger and multi‐center investigations are needed to confirm these data.